SUPPORT FOR THE LEADERSHIP FOR LEARNING IN SECONDARY EDUCATION. THE CASE OF THE SCHOOL COUNSELORS IN SPAIN - Domingo, Jesus; Caballero, Katia; Barrero, Beatriz (European Scientific Journal, ESJ, 2013)
This paper show the results of a project I+D, funded by Ministry of Education, which is focused on how support leadership for learning in Secondary schools (Ref. EDU2010-16131). The main target is to redefine and promote the relationship between principal and school counselor to develop a distributed leadership for learning towards educational community. This relationship must be based on sharing effort and commitment through a common educational project headed to get quality and equity for all. It has been used a method focused on deep biographical interview to key informants at schools. The results obtained prove there are controversial but also a good potential in this professional relationship. They must collaborate and not compete for leadership, balancing lines of action to achieve the improvement at school. In this sense, it is necessary to promote the principal’s training for the effective leadership and to redefine the counselor’s functions.